ALTERNATİF ÇATIYA GÖRE FOKAL EĞRİLER - BELHAN, GÜLŞAH (Fırat Üniveristesi, 2024)
Öklid uzayında eğriler farklı çatılara göre birçok çalışma ile incelenmiştir. Araştırmacılar eğrileri incelerken Frenet çatı, Bishop çatı, Alternatif çatı, gibi çatıları çalışmışlardır. Bu çatılar eğriler ile ilgili karakterizasyonlarda bize yardımcı olurlar. Bu tezin amacı, 3-boyutlu Öklid uzayında alternatif çatıya göre fokal eğrileri araştırmaktır. Bu amaç doğrultusunda, önce alternatif çatı tanımlandı. Daha sonra bu çatıya bağlı olarak fokal eğriler verildi ve çeşitli karakterizasyonlar elde edildi.

Curves in Euclidean space have been examined in many studies according to different frameworks. While examining curves, researchers studied frameworks such as the Frenet frame,Bishop frame and Alternative frame. These framehelp us withcharacterizations of curves. The aim of this thesis is to investigate focal curves according to alternative framework in 3-dimensional Euclidean space. For this purpose, an alternative frame was first defined. Then, focal curves were given depending on this frame and various characterizations were obtained.
Focal curves according to the alternative frame
Keywords: Matematik